lmportance of the dermatologist for the family peace. - Mazzotta, F.; Garofalo, L.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2018)
A 2-year-old baby girl with relapsing ecchymotic lesions of the face was reported. The various diagnostic hypotheses included "child abuse", a diagnosis with important psychological repercussions, were discussed. The histological examination ruled out the diagnosis of child abuse showing a deep lymphangioma.